2007
DOI: 10.1002/chem.200700527
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydrogenations One by One: Differentiation of up to Three β‐Ketocarboxylic Acid Derivatives Based on Ruthenium(II)–Binap Catalysis

Abstract: Noyori-type reductions of pairs of beta-ketoamides and beta-ketoesters with elemental hydrogen (4 bar) proceeded substrate by substrate. When Et(2)NH(2) (+)[{RuCl(S)-binap}(2)](mu-Cl)(3)(-) was employed as a catalyst in a methanol or ethanol solution, the substrates were reduced at room temperature in the order beta-ketopyrrolidide > or = beta-ketopiperidide > or = beta-keto(N,N-diethylamide) > beta-keto(alkyl esters) > beta-keto(oligofluoroalkyl esters). This is the first time that beta-ketoamides have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…When ethyl 10-morpholino-3,8,10-trioxodecanoate ( 7 ) was subjected to the same conditions (20 bar of H 2 , 70 °C, 15 h), only the β-carbonyl to the amide was saturated with 97.7% ee (Scheme , confirmed by 1 H– 13 C HMBC experiment; see Supporting Information). This excellent regio- and enantioselectivity is the first example of asymmetric monohydrogenation of bis(β-ketocarboxylic acid) derivatives. , …”
mentioning
confidence: 78%
See 1 more Smart Citation
“…When ethyl 10-morpholino-3,8,10-trioxodecanoate ( 7 ) was subjected to the same conditions (20 bar of H 2 , 70 °C, 15 h), only the β-carbonyl to the amide was saturated with 97.7% ee (Scheme , confirmed by 1 H– 13 C HMBC experiment; see Supporting Information). This excellent regio- and enantioselectivity is the first example of asymmetric monohydrogenation of bis(β-ketocarboxylic acid) derivatives. , …”
mentioning
confidence: 78%
“…Brückner et al concluded that β-ketocarboxylic acid derivatives with more electron-rich C(O)NR 2 moieties had a faster onset hydrogenation rate than those with C(O)OR by studying their rate differences in alcohols with [RuCl 2 ( S )-BINAP] 2 ·NEt 3 under relatively mild conditions (4 bar of H 2 , ambient temperature) . They also mentioned that the conclusion was based on their specified conditions.…”
mentioning
confidence: 99%
“…25), 加 氢反应 速率 取决于 取代 基 C( = O)-Het 的电子性质, 吸电子性基团的速率大, 具体顺序 为 β-酮基吡咯烷>β-酮基哌啶>β-酮基-N,N-二乙基胺 >β-酮基烷基酯>β 酮基低聚氟代烷烃酯. 反应机理如 Scheme 13 所示, 其中涉及 Ru-H 化合物 54 以及与 β-酮 基羧酸衍生物分子发生交换反应, 生成较为稳定的化合 物 55, 随后 55 在加氢速率决定步骤中被消耗完毕, 并 释放出产物[58] .得到定量转化产率和 70%~91% ee(Eq. 26).…”
unclassified
“…Catalytic asymmetric hydrogenation of b-keto amides is an efficient approach to the synthesis of optically pure chiral b-hydroxy amides, [14] which are useful building blocks for the synthesis of biologically active compounds. For example, the optically pure chiral b-hydroxy amide 5 a (R = Me) has been used in the enantioselective synthesis of the antidepressants fluoxetine and tomoxetine [15] (Scheme 2).…”
mentioning
confidence: 99%